2004
DOI: 10.1097/00019605-200404000-00009
|View full text |Cite
|
Sign up to set email alerts
|

Mosaic trisomy 22 in a boy with a terminal transverse limb reduction defect

Abstract: A terminal transverse limb reduction defect is a relatively common congenital malformation that most often occurs unilaterally and in isolation. A mildly mentally disabled boy is described with an absent left hand, a congenital cardiac defect, short stature, facial dysmorphism and skin pigmentary anomalies. Karyotyping of fibroblasts revealed mosaic trisomy 22. Most of the clinical features of our patient are consistent with the phenotype of mosaic trisomy 22, however, a terminal transverse reduction defect ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(21 citation statements)
references
References 15 publications
0
20
0
1
Order By: Relevance
“…Body asymmetry and 5th finger clinodactyly were the most common abnormalities seen in 62% and 43%, respectively. A third of the patients had linear pigmentary changes along Blaschko lines, of which some were diagnosed as hypomelanosis of Ito [Wertelecki et al, ; Ruiter et al, ; Merks et al, ; Thomas et al, ; Woods et al, ; Lewis et al, ]. Both pigmentary changes and asymmetric growth are associated with chromosomal mosaicism [Woods et al, ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Body asymmetry and 5th finger clinodactyly were the most common abnormalities seen in 62% and 43%, respectively. A third of the patients had linear pigmentary changes along Blaschko lines, of which some were diagnosed as hypomelanosis of Ito [Wertelecki et al, ; Ruiter et al, ; Merks et al, ; Thomas et al, ; Woods et al, ; Lewis et al, ]. Both pigmentary changes and asymmetric growth are associated with chromosomal mosaicism [Woods et al, ].…”
Section: Discussionmentioning
confidence: 99%
“…Also of significance, all patients reported before 2003 [Wertelecki et al, ; Lessick et al, ; Woods et al, ; De Pater et al, ; Basaran et al, ; De Ravel et al, ] had some degree of developmental delay. IQ was reported in three patients and it ranged from 55 to the low 80s [Wertelecki et al, ; Ruiter et al, ; Lewis et al, ], suggesting the potential for ascertainment bias. We therefore caution that mildly affected patients may be under diagnosed, resulting in ascertainment bias and skewing in prognosis of this condition.…”
Section: Discussionmentioning
confidence: 99%
“…A total of 20 previously reported patients with mosaic trisomy 22 were reviewed and compared with our patient [Mollica et al, 1977; Osztovics and Ivady, 1977; Pagon et al, 1979; Dulitzky et al, 1981; Schinzel, 1981; Zhang et al, 1984; Wertelecki et al, 1986; Lessick et al, 1988; Lund and Tranebjaerg, 1990; Woods et al, 1994; Pridjian et al, 1995; Crowe et al, 1997; de Pater et al, 1997; Berghella et al, 1998; Basaran et al, 2001; Ruiter et al, 2004; Thomas et al, 2004; Florez and Lacassie, 2005]. As shown in Table I, the clinical features in our patient are consistent with previous reports.…”
Section: To the Editormentioning
confidence: 99%
“…Hemiatrophy was seen in 11/16 patients. Moreover, major deficiency, such as terminal transverse limb reduction [Ruiter et al, 2004] and radial aplasia [Dulitzky et al, 1981] were reported.…”
Section: To the Editormentioning
confidence: 99%
“…Entre sus características principales se destaca la hipoplasia facial con puente nasal plano y ancho, orejas displásicas con pits preauriculares, paladar hendido, hipertelorismo, microcefalia o alteraciones craneales, enfermedad cardiaca congénita, alteraciones urogenitales y RCIU (12,18). Por otra parte, en pacientes con trisomía 22 tipo mosaico se presenta frecuentemente hemiatrofia, defectos por reducción transversa de extremidades, sindactilia, hipomelanosis de Ito, hipoacusia neurosensorial o conductiva y retardo mental (12,19,20).…”
Section: Discussionunclassified